(untitled) (Journal of the Bangladesh Agricultural University, 2012)
The present study was an attempt to analyze the farmers perception about causes and remedies of Monga in some selected areas of Lalmonirhat district of Bangladesh. In order to achieve the objectives, survey was conducted in three villages and one Char area in Hatibandha upazila of Lalmonirhat district. In total 90 samples were purposively taken of which 45 were from Char area, 25 from rural area, and 20 from urban area. The family size of the respondents revealed that medium family domination in Char area (the poorest area) is an indication of the consciousness of the poor people about population problem. Monga stricken people in terms of less consumption were higher in Char and rural areas compared to urban area. Lack of cultivable land, natural calamities, nonavailability of working facilities at non-agricultural sector, lack of working facilities at agricultural sector due to natural calamities and lack of credit availability and high interest rate were opined by the researcher as their causes of Monga. On the other hand, beef fattening, petty business, plant nursery and poultry farming were addressed as the mitigating activities of Monga undertaken by NGOs. old-age allowance, Hundred-days job scheme and Vulnerable Group Development (VGD) programme were observed as Monga mitigating activities undertaken by GOs in the study area. The difference between the performance of GO and NGO in Monga mitigation was wider in Char area than that of in rural and urban areas. The higher performance of NGOs was due to their better identification, selection and supervision strategy with perfect information. Drawbacks like, corruption, lack of proper management, lack of adequate financial support, etc., might be responsible for the poor performance of GO mitigating activities of Monga in the study area. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12101 J. Bangladesh Agril. Univ. 10(1): 107118, 2012